Improved forage-based feeding systems for smallholder livelihoods in the Cambodia-Laos-Vietnam development triangle - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
This project will focus on improving smallholders’ production skills, increasing demand awareness, and establishing effective and efficient linkages among value-chain stakeholders to gain wider market access.